Molecular epidemiology of rotavirus A in Iranian broiler flocks - NAZARPAK, HADI HAGHBIN; HOSSEINI, HOSSEIN; GHALYANCHILANGEROUDI, ARASH; MORSHED, RIMA (The Indian Journal of Animal Sciences, 2018)
Avian rotaviruses (RV) are still largely undefined despite being widespread in several avian species and significant economic the impact of rotavirus enteritis in poultry flocks. In this study, the presence of avian RV groups was investigated in 36 commercial poultry flocks with a history of enteric diseases in Iran. Intestinal contents of broiler chickens with diarrhea and stunting syndrome were analyzed by reverse transcription-polymerase chain reaction specific for RVs based on NSP4 gene. Through partial sequencing and BLAST analyses of 11 positive specimens, we identified avian-like RV group A (RVA) strain. There was high prevalence of group A rotaviruses (approximately 30%) in our samples. The phylogenetic analysis also revealed a close genetic relationship between the current isolates and other avian RVAs but located in the separate cluster. This study provides novel data on the prevalence of genetically different avian RVs in Iranian poultry flocks.